2022
DOI: 10.1039/d2cp03889g
|View full text |Cite
|
Sign up to set email alerts
|

The activated reaction of dichlorocarbene with triplet molecular oxygen

Abstract: The reaction of dichlorocarbene and molecular oxygen in their respective ground states is hindered by a considerable barrier rendering a diffusion controlled formation of the resulting Criegee intermediate unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Our lab has shown that this results in unusual chemistry, such as a preference for least-motion reactions with H 2 and alkenes 12 as opposed to other ordinary carbenes 13,14 as well as a swift reaction with triplet oxygen at cryogenic temperatures 15 despite the commonly encountered spin state selectivity of carbenes. 16,17…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our lab has shown that this results in unusual chemistry, such as a preference for least-motion reactions with H 2 and alkenes 12 as opposed to other ordinary carbenes 13,14 as well as a swift reaction with triplet oxygen at cryogenic temperatures 15 despite the commonly encountered spin state selectivity of carbenes. 16,17…”
mentioning
confidence: 99%
“…Our lab has shown that this results in unusual chemistry, such as a preference for least-motion reactions with H 2 and alkenes 12 as opposed to other ordinary carbenes 13,14 as well as a swift reaction with triplet oxygen at cryogenic temperatures 15 despite the commonly encountered spin state selectivity of carbenes. 16,17 A major breakthrough in the chemistry of s 0 p 2 carbenes has recently been accomplished with the isolation of rhodium-Fig. 1 The usually high-lying s 0 p 2 configuration of carbenes (A) becomes the ground state in 2 (B) and 4 (C) facilitating their unusual chemistry.…”
mentioning
confidence: 99%